The impact of the quality of communication from nephrologists to primary care practitioners: A literature review - Jiwa, M.; Chakera, Aron; Dadich, A.; Ossolinski, G.; Hewitt, V. (Informa Healthcare, 2014)
© 2014 Informa UK Ltd. Objective: This review of the literature aims to explore two research questions: (1) what is the evidence that patients benefit from sound communication between primary care practitioners (PCPs) and nephrologists; and (2) what information is required in primary care to meet the needs of patients who have attended a renal unit? Research design and methods: Fifty-seven citations were independently reviewed by four authors. The inclusion criteria were: (1) the article focused on information flow from nephrologists and/or specialists to general practitioners; (2) it includes the involvement of PCPs in nephrology, including registrars and PCPs with special interests or specialists in any medical field; (3) it was published from 1990 onwards (inclusive) and (4) the study was conducted in the United Kingdom, Canada, The Netherlands, Australia, United States or New Zealand. Selected articles were then reviewed by the fifth author as a measure of inter-rater reliability. Results: Eighteen papers in four categories were identified: six audits or observational studies, one meta-analysis; one randomized controlled trial; six qualitative studies; and four position statements or quality improvement tools. Published audits involving feedback to clinicians using validated tools demonstrate the scope for substantial improvement in the amount of information relayed to PCPs. Specialists may not prioritize the letter to the PCP but there is some evidence of a direct impact from limited or inadequate communication on patient outcomes. Only two studies focused on patients attending nephrology clinics. Conclusions: There is some evidence that improving the quality of letters from specialists to PCPs may benefit patient care. This review suggests a need for research on communication from nephrologists about patients who have received care at a renal unit regardless of whether or not the patient continues to attend.